273 Effect of Feedlot Implant Dose and Terminal Window Timing on Heifer Performance and Carcass Characteristics. (7th May 2021) - Pyatt, Nathan; Vogel, Gary; Brown, Mike; White, Frank; Kayser, William; Homm, Justin; Herr, Cory; Holland, Ben; Word, Alyssa
Abstract: Feedlot heifers (n = 3, 778; initial BW = 310 kg; SD = 28 kg) were utilized in a 3 x 2 factorial arrangement (9 pens/treatment) to investigate increasing implant dose and terminal window (TW) timing on growth and carcass merit. Component with Tylan® implant dose treatments were 1. Initial TE-IH [80 mg trenbolone acetate (TBA), 8 mg estradiol (E2)] and terminal TE-H (140 mg TBA, 14 mg E2; IH/H), 2. Initial TE-IH and terminal TE-200 (200 mg TBA, 20 mg E2; IH/200), or 3. Initial TE-200 and terminal TE-200 (200/200). Heifers were fed 171 d with terminal implant administered 100 or 60 d prior to slaughter; initial implant window was inverse (71 or 111 d) to TW. Data were analyzed as a mixed model with block included as a random effect. No significant dose x TW interactions occurred for growth or carcass characteristics (P ≥ 0.06) therefore, main effects are presented. Terminal window treatments resulted in similar (P > 0.25) live performance. Heifers reimplanted 60 d prior to slaughter had improved (P < 0.05) marbling score and lower YG2 carcasses. Final weight, gain, HCW, yield, and LM area increased (linear; P < 0.05), while marbling score and fat thickness decreased (linear; P < 0.05) with increasing heifer implant dose. Heifers implanted with IH/200 had lower (P < 0.05) DMI compared to IH/H. IH/200 and 200/200 had improved (+2.1%; P < 0.05) efficiency compared to IH/H. HCW for 200/200 was +3.2 and 5.5 kg greater than IH/200 and IH/H, respectively. 200/200 were leaner with +7.4% YG 1&2 and -5.4% YG 4&5, but -8.5% Prime & Choice carcass compared to IH/H. Shortening TW from 100 to 60 d prior to slaughter did not alter growth performance. Increased implant dose in heifers improved gain, efficiency, HCW and yield with some quality grade considerations.